Coastal Surveillance and Water Quality monitoring in the Rejiche Sea-Tunisia - Alibi, Sana; Beltifa, Asma; Hassen, Wafa; Jaziri, Ahlem; Soussia, Lotfi; Zbidi, Fairouz; Ben Mansour, Hedi (Water environment research, 2021)
The aim of this study is to determine physiochemical and bacteriological properties of seawater and sediments from the coast of Tunisia during six successive months. The conductivity was measured using previously calibrated Hach Conductivity meter. Total suspended solid was determined using Whatman GF/C glass fiber filter (Sigma Aldrich), and the turbidity was assessed using a spectrophotometer (UV/Vis). The pH was measured using pH electrodes. Other physiochemical parameters were determined using Pastel UV multiparameter water analyzer (Secomam, aqualabo). Bacterial analysis was displayed by membrane filtration method, and isolates were identified to the species level by Api strips. Susceptibility to antibiotics was determined by disk diffusion methods. Total suspended solid, turbidity, adsorbable organic halogen, chemical oxygen demand, and biochemical oxygen demand were higher than accepted norms in Tunisia. Enterococcus faecalis was detected in all the sites indicating a human fecal contamination, and all the isolates were highly resistant to rifampicin, gentamicin, chloramphenicol, ampicillin, and azithromycin. The situation in Mahdia coast is alarming particularly with the isolation of multidrug resistance strains. It is recommended that the local government provide restrict policies for the treatment and the assessment of municipal wastewater before its discharge into sea. PRACTITIONER POINTS: Coastal Surveillance and Water Quality monitoring in the Rejiche Sea - Tunisia is crucial. Enterococcus faecalis was detected in sea water and sediment samples in the coast of Rejiche. Isolated strains were highly resistant to rifampicin, gentamicin, chloramphenicol, ampicillin and azithromycin.